Elitical And Antidemocratic Transformational Leadership Critics: Is It Still Relevant ? ( A Literature Study) - Masduki Asbari; Priyono Budi Santoso; Agustian Budi Prasetya (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
This paper aims to analyze the statements of Bass & Riggio (2006) regarding criticisms of the transformational leadership style which is often considered elitist and anti-democratic. Is the Transformational Leadership style still relevant to today's increasingly dynamic era with the increasing complexity of the organizational environment. With the analysis model using literature study methods from several relevant journals, the results of the analysis show that there is still a strong relevance between transformational leadership patterns and the company's desire to innovate. Transformational leadership is able to maintain continuous and sustainable organizational innovation. Making organizations more agile is also discussed in this article as an antecedent of organizational innovation.